Идентификация параметров математической модели авиационного двигателя Д-436 по результатам наземных стендовых испытаний - Антипцев, Ю. П.; Аннопольская, И. Е.; Степанов, И. Ю. (Eastern-European Journal of Enterprise Technologies, 2009)
Methodic and identification parameters and characteristics results of mathematical model (MM) for aviation gas-turbine engine D-436 SE ‘Ivchenco – Progress” by experimental data are presented